Pengaruh Rasio Keuangan Terhadap Kinerja Keuangan Perusahaan yang Terdaftar di Bursa Efek Indonesia (Sub Sektor Makanan dan Minuman Periode 2015-2020) - Bintang Rahmat Firmansyah; YuniYuniningsih Yuniningsih (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Tighter competition, cannibalism between companies, inflation, faster technological developments, growing attention to environmental factors, economic crises, and social responsibility force financial managers to act as general managers. Financial managers must be able to translate strategic objectives in determining the financial performance of a company. Financial managers must be able to make decisions in achieving the optimal level of profit. Efficiency in financing investment will be reflected in the acquisition of data with minimal costs, while the optimal dividend policy will be reflected in increasing prosperity and company achievement. The purpose of this study is to empirically prove the effect of financial ratios (Investment, Growth, Liquidity and Dividends) on company's financial performance. This research is a quantitative research using secondary data obtained from the company's annual report. The population in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2020 period as many as 15 companies. The sampling technique in this study used purposive sampling. There are 11 companies that meet the criteria in this study. The data analysis technique used is multiple linear regression analysis using SPSS 17.0 for Windows. The results of this study indicate that partially the ratio of investment, growth and dividends has a positive and significant influence on the company's financial performance and liquidity does not have a positive and significant effect on the company's financial performance results.